International Monetary Fund Annual Report 1985. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1985)
This paper reviews the IMF's Annual Report for the fiscal year ended April 30, 1985. The report highlights that by mid-1985, economic recovery in the industrial countries had been under way, although unevenly, for some two and a half years. Output growth in 1984 was the strongest in almost a decade, and inflation continued to recede. There were encouraging signs that the benefits of this recovery were spreading to the developing world. Aided by the improved external environment and the increased firmness with which adjustment policies were pursued, domestic growth rates in developing countries accelerated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet